SISTEM INFORMASI PEMESANAN BARANG DENGAN METODE EOQ TERHADAP PEMBERIAN DISKON PADA TOKO MULTI AGUNG - Riswandy Tiryasuwiryo; Sudirman; Arfan Yunus (JTRISTE, 2019)
All this time Multi Agung shop had problems with the amount of goods that available are not coordinated and doesn’t utilizing the discount offer given by supplier. This research aim’s to implement EOQ Method to the goods ordering information system at Multi Agung shop and apply EOQ Method toward discounting to the goods ordering information system at Multi Agung shop. The used method is Economic Order Quantity (EOQ). In calculating EOQ, variables such as annual demand, ordering cost per order, and holding cost per unit is used. In analyzing the discount offer, this method takes into account purchase cost of each unit of goods. From the data processing for foolscap, the EOQ result was 120 reams which produce total cost (TC) of Rp133,394,388. Compared to EOQ, the offer of 2250 reams to get 1% discount from supplier produce lower TC with Rp130,449,433. Therefore, 2250 reams are the most optimal order quantity. The application of EOQ method toward discounting to the goods ordering information system at the Multi Agung shop has been successful. The system can analyze the discount offer from supplier, so that this sytem can be used by Multi Agung shop in taking decision for optimal order quantity based on the total cost that avaiable at the store.